Anti-protein C antibodies and acquired protein C resistance in SLE: novel markers for thromboembolic events and disease activity?. (23rd September 2020) - Ramirez, Giuseppe A; Mackie, Ian; Nallamilli, Susanna; Pires, Tatiana; Moll, Rachel; Pericleous, Charis; Isenberg, David A; Cohen, Hannah; Efthymiou, Maria
Abstract: Objectives: Risk factors for thromboembolism in SLE are poorly understood. We hypothesized a possible role for protein C, based on its dual activity in inflammation and haemostasis and on the evidence of an association between acquired activated protein C (APC) resistance (APCR) and high-avidity anti-protein C antibodies (anti-PC) with a severe thrombotic phenotype in venous thrombosis APS patients. Methods: In a cross-sectional study of 156 SLE patients, the presence and avidity of IgG anti-PC was established by in house-ELISA, and APCR to exogenous recombinant human APC (rhAPC) and Protac (which activates endogenous protein C) was assessed by thrombin generation-based assays. Associations with aPL profile, thrombotic history and disease activity (BILAG and SLEDAI-2K) were also established. Results: Anti-PC were detected in 54.5% of patients and APCR in 59%. Anti-PC positivity was associated with APCR to both rhAPC ( P   <0.0001) and Protac ( P  =0.0001). High-avidity anti-PC, detected in 26.3% of SLE patients, were associated with APCR in patients with thrombosis only ( P  <0.05), and with the development of thrombosis over time (range: 0–52 years; P  =0.014). High-avidity anti-PC levels correlated with SLEDAI-2K ( P  =0.033) and total BILAG ( P  =0.019); SLEDAI-2K correlated inversely with APCR to Protac ( P  =0.004). Conclusion: Anti-PC occur in patients with SLE, independently of aPL profile, and are associated with APCR. High-avidity anti-PC are associated with thrombosis and with active disease and might prove a novel marker to monitor the risk of thrombosis and disease progression in SLE.